1989
DOI: 10.7547/87507315-79-6-263
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of Aloe vera against a spectrum of irritants

Abstract: The authors have evaluated the spectrum of anti-inflammatory activity of A. vera in a number of models of inflammation in the hind paw of the experimental rat induced by kaolin, carrageenan, albumin, dextran, gelatin, and mustard. Croton oil was used in a topical model of inflammation to determine the oral activity and time-dependent dosing of A. vera. The authors found that A. vera was active in all models of inflammation. Of the various irritants tested, A. vera was especially active against gelatin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…It has been shown that in experimental animals Aloe vera reduces inflammation detected as reduced neutrophil migration and edema formation (Davis et al, 1989). In Helicobacter pylori-infected rats Aloe vera significantly reduced leukocyte adhesion and TNF␣ levels (Prabjone et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in experimental animals Aloe vera reduces inflammation detected as reduced neutrophil migration and edema formation (Davis et al, 1989). In Helicobacter pylori-infected rats Aloe vera significantly reduced leukocyte adhesion and TNF␣ levels (Prabjone et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It improved healing by increasing the blood supply, which increased oxygenation as a result [13]. Davis et al, in his study examined the possibility of aloe gel being an active growth substance as mannose-6-phosphate was the major sugar in aloe gel [14].…”
mentioning
confidence: 99%
“…Moreover, the healing powers of AV through high-molecular-weight polypeptide constituent from the gel demonstrated a healing effect on excisional wounds in rats. [15] Yagi et al [16] reported that AV gel contains a glycoprotein with cell proliferating-promoting activity, while Davis et al [17] noted that AV increasing blood supply, which increased oxygenation as result. [18] As regarded to erythema score among study groups at different times, decreased in both types of AV.…”
Section: Discussionmentioning
confidence: 99%